Rally effects, threat, and attitude change an integrative approach to understanding the role of emotion. [article]. - Lambert, Allan J.
Rally 'round the flag effects (J.E. Mueller, 1970) represent sudden and dramatically powerful situation-specific shifts in attitudes toward the American president. However, the extant literature has yet to fully clarify the nature of the psychological dynamics associated with this effect. These ambiguities reflect fundamental differences of opinion among scholars on some very basic questions such as whether overtly experienced emotion should mediate these attitudinal shifts in conservative ideology. Across 4 experiments, the authors sought to gain greater clarity on these and other important matters using multimethod approach in which the authors varied whether participants viewed documentary footage of the 9/11 attacks (Experiment 1-2), generated autobiographical memories of that event (Experiment 3), or retrieved nonpolitical memories from their past (Experiment 4). The authors discuss the relevance of the present findings for theory and research across variety of different theoretical and methodological paradigms, including social psychological models of threat, emotional appraisal models, and the political science literature. -- (from the author)
Keywords: Threat; Emotion; Political attitudes; 'Round the flag